Analisa Dan Perancangan Sistem Informasi Akademik - Rizky Yoga Pratama (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
School is a form of educational institution in which teaching and learning activities take place, as well as various other activities carried out in the teaching and learning process. These teaching and learning activities are interrelated with several elements such as teachers, students, and subject matter that are connected in a school curriculum. This researcher examines the development of information system at Junior High School. Researchers want to design an information system using the PHP and Mysql programming languages and testing this application using the Black Box method. This system is expected to simplify and speed up the processing of data or information, as well as support the implementation of teaching and learning activities in schools. It is hoped that this system can be developed by registering new year admissions and conducting regular maintenance.